Water for human and livestock consumption in rural settings of Ethiopia: Assessments of quality and health aspects - Amenu, K.; Markemann, A.; Zarate, A.V. (Springer, 2013)
The study aimed to assess the quality and health aspects of water intended for human and livestock consumption in two rural districts of the Rift Valley of Ethiopia. The study involved two parts: the first consisted of a questionnaire survey and farmers’ group discussions, complemented by secondary health data, and the second part determined the chemical (total dissolved solids, pH, manganese, hexa-valent chromium, fluoride) and microbiological quality of different water sources during dry and wet seasons. The result showed a lack of sustainable access to safe water in the communities. Industrial pollution and mismanagement of water sources by human and livestock was found to be a source of potential health risk. Potentially linked human health problems like malaria, diarrhoea and gastrointestinal parasites were common in the districts. Overall, 76 % of the assessed water sources (n = 25) failed to comply with World Health Organization guidelines for human drinking water, for at least one assessed parameter, mostly irrespective of the season. The non-compliance was mainly attributed to Escherichia coli contamination and/or high fluoride concentration. At least 20 % of the water samples were also found to be unfit for livestock consumption based on assessed chemical parameters in both dry and wet seasons. To minimize the health risk associated with mismanagement and poor quality of water sources in the area, targeted action in the protection of surface water sources should be given priority.